Shoulder Latarjet Procedure Using All-Suture Anchor and Button Fixation - Daniela Gutiérrez-Zúñiga, M.D.; Steven Otálvaro, M.D.; Giuseppe Alajmo, M.D.; Felipe José Valbuena, M.D., M.Ed.; Mauricio Largacha, M.D., F.A.A.N.A. (Arthroscopy Techniques)
The Latarjet procedure is a widely used and effective approach for treating anterior shoulder instability. However, hardware-related complications are a potential risk of the procedure for issues such as screw prominence, breakage, pain, or neurologic injury. To address these challenges, fixation with suture buttons, cerclage, or anchors has been proposed to reduce screw-related complications or revision procedures. Although these methods have shown promising results, they often require access to the posterior glenoid via an arthroscopic approach, which can be technically demanding. Biomechanical studies support the efficacy of all-suture anchors in achieving reliable fixation without compromising stability. This article presents an alternative fixation for the open Latarjet technique using all-suture anchors and suture buttons, eliminating the need for screws and additional posterior access.